A Case Study Of Pfizer Inc - Louis, Gerard Felix (2006)
Pfizer's actions, positions, strategies are discussed in depth in the case study. It describes how pfizer has positioned itself at the number one spot in the pharmaceutical industry worldwide and how it continues to defend that position.